Routledge handbook of Asian demography - Zhao, Zhongwei; Hayes, Adrian C.; Goodkind, Daniel
"Home to close to 60 per cent of the world's population, Asia is the largest and by far the most populous continent. It is also extremely diverse, physically and culturally. Asian countries and regions have their own distinctive histories, cultural traditions, religious beliefs and political systems, and they have often pursued different routes to development. Asian populations also present a striking array of demographic characteristics and stages of demographic transition. This handbook is the first to provide a comprehensive study of population change across the whole of Asia. Comprising 28 chapters by more than 40 international experts this handbook examines demographic transitions on the continent, their considerable variations, their causes and consequences, and their relationships with a wide range of social, economic, political and cultural processes. Major topics covered include: population studies and sources of demographic data; historical demography; family planning and fertility decline; sex preferences; mortality changes; causes of death; HIV/AIDS; population distribution and migration; urbanization; marriage and family; human capital and labour force; population ageing; demographic dividends; political demography; population and environment; and Asia's demographic future"--